Melodies that live in our hearts: intentional harmonies and rhythms within the inspiring teacher - Fielding, Julie Maree (Curtin University, 2009)
The interpretative narratives that lie within the pages of this study tell the story of a teacher who seeks to find the heart and soul of her teaching practice. Represented as soundscapes the stories evoke a consciousness of sound, the sound of learning. As she journeys through times of fear, confrontation with violence, loss of self-confidence, and depression, she opens her eyes to the harsh realities within the world of education, a world that appears to deny humanness through its preoccupation with objective measurement. As she focuses on what it is to be a teacher of students she views the outside world as incomprehensible in its absurdity.Illuminating encounters expose understandings and insights as she deliberately reflects on her narratives, engages in scholarly reading, thinking and writing. She particularly draws upon her deeply-held beliefs for the democratic principles of teaching.This is the story of a teacher who searches deeply for understanding amidst the minds of writers who help make sense of her world. They offer optimistic pathways to possible realms of education where the identity, integrity and humility of everyone who participates within these worlds with her can be honoured.This teacher is moved by the passions that stir in her heart. The passion for art and music sensitises her towards the aesthetic, artistic and spiritual possibilities of teaching. As she embraces her spirituality and awareness, an inner sense of the higher self to which she can appeal to for insight, wisdom, comfort, peace, calm and a clear mind she aspires to capture a teacher’s reflection in the mirror of these narratives. She hopes teachers might see a reflection of themselves within the stories, stories that resonate and add to self-understanding.This teacher draws twenty-first century learners, guiding from the side, towards the possibilities for advancing in technology. She sees fearsome consequences that a lack of moral thought and deliberation could put young people, who are barraged by superficial modes of technological communication, at risk, becoming unguided by thoughtful, moral purpose. As the gaps between student and teacher grow exponentially, she still has an optimistic energy for the possibilities of reconnecting hearts and souls in education.She has a desire to reveal the confronting life of a teacher who struggles daily to maintain her integrity and honesty whilst remaining humble before all these confrontations. This desire has empowered her quest to understand what lies at the heart of a good teacher.This is Jodie’s story, my story, a story that many others may have written, yet so far unwritten by many teachers.